Beyond the Liver: Liver-Eye Communication in Clinical and Experimental Aspects - Yuan, Tian-Hao; Yue, Zhen-Sheng; Zhang, Guo-Heng; Wang, Lin; Dou, Guo-Rui (Frontiers in Molecular Biosciences, 2021)
The communication between organs participates in the regulation of body homeostasis under physiological conditions and the progression and adaptation of diseases under pathological conditions. The communication between the liver and the eyes has been received more and more attention. In this review, we summarized some molecular mediators that can reflect the relationship between the liver and the eye, and then extended the metabolic relationship between the liver and the eye. We also summarized some typical diseases and phenotypes that have been able to reflect the liver-eye connection in the clinic, especially non-alcoholic fatty liver disease (NAFLD) and diabetic retinopathy (DR). The close connection between the liver and the eye is reflected through multiple pathways such as metabolism, oxidative stress, and inflammation. In addition, we presented the connection between the liver and the eye in traditional Chinese medicine, and introduced the fact that artificial intelligence may use the close connection between the liver and the eye to help us solve some practical clinical problems. Paying attention to liver-eye communication will help us have a deeper and more comprehensive understanding of certain communication between liver diseases and eyes, and provide new ideas for their potential therapeutic strategy.